Analisis Realisasi Anggaran Kas Sebagai Alat Perencanaan dan Pengendalian Kas Bagian REN BNN Sumatera Utara - Nurul Maghfirah; Juliana Nasution (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2022)
This research aims to understand the process of budgeting, the factors of forming cash budgeting, and how the realization of budgeting as planning and controlling cash in REN BNN Sumatera Utara. This research is a qualitative study with observation, study documentation method, and descriptive analysis. The research shows that cash budgeting and realization budgeting of REN BNN Sumatera Utara from the previous year is the main factor to arrange to budget for the next year. The realization of cash budgeting as a tool and controlling cash of REN BNN Sumatera Utara in 2018-2020 is considered quite good because the difference between budgeting and realization budgeting is Favorable, reasonable, and can be anticipated.